Efficacy of a minimal home-based psychoeducative intervention in patients with advanced COPD: A randomised controlled trial. (December 2016) - Bove, D.G.; Lomborg, K.; Jensen, A.K.; Overgaard, D.; Lindhardt, B.Ø.; Midtgaard, J.
Abstract: Background: Anxiety is a common comorbidity in patients with advanced Chronic Obstructive Pulmonary Disease (COPD) with major impact on quality of life and associated with increased risk of death. The objective of this randomised controlled trial was to test the efficacy of a minimal home-based psychoeducative intervention versus usual care for reducing symptoms of anxiety in patients with advanced COPD. Methods: The trial included 66 participants with advanced COPD and symptoms of anxiety. The primary outcome was anxiety assessed by the Hospital Anxiety and Depression scale (HADS) subscale for anxiety (HADS-A). The secondary outcome was mastery assessed by the Chronic Respiratory Questionnaire (CRQ) domain of mastery (CRQ-M). Assessments were performed at baseline and one and three months post-intervention. Results: The intervention group had a lower post intervention HADS-A score on average, compared with the control group (p = 0.005), indicating a significant effect of the intervention. The average difference between the groups in HADS-A was 2.16 points (CI = [0.62; 3.71]) at one month and 2.32 points (CI = [0.74; 3.89]) at three months follow-up. The intervention group had a higher post intervention CRQ-M score on average compared with the control group (p = 0.016). The average differences between the groups were 0.58 points (CI = [0.09; 1.06]) after one month and 0.67 points (CI = [0.18; 1.17]) after three months. Conclusions: The psychoeducative intervention provided sustainable symptom relief and improved the patients' self-management abilities. Highlights: This paper contributes with new knowledge in the form of a supportive self-management intervention developed to address the special needs of patients with advanced COPD. This paper demonstrates that a minimal home-based psychoeducative intervention reduces symptoms of anxiety and increase mastery in patients with advanced COPD. This paper shows that it is possible, albeit with some challenges, to conduct intervention studies with patients with advanced COPD and a high symptom burden.